Analisis Risiko Sistemik dan Keterkaitan Keuangan: Studi pada Bank Umum Syariah di Indonesia - Rihana Sofie Nabella; Ghozali Maski; Setyo Tri Wahyudi (Journal of Business & Banking, 2020)
Islamic banking in Indonesia has developed as indicated marked by the establishment of Bank Muamalat Indonesia as the first Islamic bank in Indonesia. Islamic banks—Besides the conventional bansk— are an alternative source of financing which are expected to support the country's economic growth. Banks are also known as risk-prone institutions, one of which is systemic risk. This study aims to measure systemic risk and financial linkages in Islamic commercial banks in Indonesia. This study uses the Conditional Value at Risk (CoVaR) model developed by Adrian and Brunnermeier (2009) with data samples of 8 Islamic banks in Indonesia from January 2012 to December 2018. The results isobtained are the contribution of systemic risk is not determined by the size of bank assets and individual risk. k, sBo that both small banks and large banks can threaten financial system stability. So that it can be a reference for regulators to always supervise all banks, not only large banks but also small banks that have high individual risks.